Good and Plenty : The Creative Successes of American Arts Funding - Cowen, Tyler (Book collections on Project MUSE., 2006)
Americans agree about government arts funding in the way the women in the old joke agree about the food at the wedding: it's terrible--and such small portions! Americans typically either want to abolish the National Endowment for the Arts, or they believe that public arts funding should be dramatically increased because the arts cannot survive in the free market. It would take a lover of the arts who is also a libertarian economist to bridge such a gap. Enter Tyler Cowen. In this book he argues why the U.S. way of funding the arts, while largely indirect, results not in the terrible and the s.